The Effect Of Stock Price, Earning Per Share, Current Year Profit, Inflation, Interest And Exchange Rate On Construction Investment In Pt. Total Bangun Persada Tbk During 2013-2022 - Sugiharto, Ugi; Astuty, Pudji (Nomico, 2024)
Indonesia is vigorously promoting progress in the construction sector, a key aspect of infrastructure development aimed at achieving equitable distribution across the country and preventing economic disparities (Willar, Waney, Pangemanan, & Mait, 2019). Infrastructure development is an essential program that continues to be advanced to enhance infrastructure and ensure economic equality throughout Indonesia. One of the primary infrastructure sectors targeted for development is construction (Pridayanti, 2014). Construction plays a vital role in supporting economic growth and improving the quality of life by providing necessary facilities and amenities. The construction of roads, bridges, buildings, and other infrastructures not only enhances connectivity and logistics efficiency but creates jobs and attracts investment. Therefore, the construction sector is a priority in the government's efforts to strengthen national competitiveness and catch up with other countries. One solution to support infrastructure development, particularly in construction, is through investment. Investment in the construction sector is crucial as it provides the necessary funds to build and improve existing and new infrastructures (Tambunan, Sabijono, & Lambey, 2019). Moreover, investment can attract reputable and competent construction companies, such as PT Total Bangun Persada Tbk, a private company engaged in construction. Investment also plays a role in creating new jobs, enhancing local workforce skills, and fostering economic growth (Mara, 2022). In making investment decisions, several factors need to be considered, such as the impact of stock prices, Earnings Per Share (EPS), current profit, inflation, interest rates, and exchange rates. Stock prices reflect the company's performance and market perception of prospects, while EPS indicates the profit earned per share, providing insight into the company's financial health. Current profit shows the profitability generated from daily operations. Inflation and interest rates are macroeconomic indicators that affect purchasing power and capital costs. Exchange rates, on the other hand, influence the cost of importing raw materials and the company's exposure to international markets. All these factors must be comprehensively considered to make wise and beneficial investment decisions.